Did the 2008 Wenchuan earthquake trigger a change in the conduct of research on seismic risk?. (May 2020) - Zhang, Qiang; Lu, Qibin; Ye, Xuanting; Xu, Shiling; Lin, Leesa K.; Ye, Qian; Zeng, An
Abstract: This study aims to address how the 2008 Wenchuan Earthquake influenced knowledge generation and diffusion compared to the research stemming from the 1989 Loma Prieta Earthquake in the United States and the 1995 Hanshin Awaji Earthquake in Japan, for the three countries are exposed to high seismic risk. The findings show that (1) regarding research quantity, the influence of the Wenchuan Earthquake on disaster-related knowledge generation is just beginning compared with the gradual decreases in research on the other earthquakes; (2) regarding disciplinary development, the proportion of studies relating to the Wenchuan Earthquake in natural sciences and engineering technology is gradually decreasing, while the proportion of studies in medical science, social sciences and economics is increasing; (3) the quantity of earthquake-related studies is not solely related to the influence of a specific disaster but associated with the national financial support offered by the affected country. One reason why China experiences the high research output is that Chinese national finance strongly supports such research, similar to the United States and Japan. This phenomenon corresponds with the fact that the major research institutions in China are national institutions rather than universities. Finally, (4) interdisciplinary research on the Wenchuan Earthquake mainly involves interactions between natural sciences and engineering technology. Interactions between other disciplines need to be enhanced. Thus, this research argues that, although disaster knowledge generation and diffusion is imbalanced, the multidimensional nature of earthquakes has been recognized in the literature.